24th ACM/IEEE Conference Proceedings on Design Automation Conference - DAC '87 1987
DOI: 10.1145/37888.37980
|View full text |Cite
|
Sign up to set email alerts
|

Statistics for parallelism and abstraction level in digital simulation

Abstract: This paper presents statistics of several designs at four design abstraction levels -the instruction, behavioral, RTL, and gate levels. The data includes simulation time profiles, maximum speedup and limitations of parallelism, typical model evaluation times, event distributions, element intensities, and component counts for the four abstraction levels. This data is then used to analyze and evaluate several speed-up approaches: mixed-level simulation, parallel software simulators, parallel pipelined hardware a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Soulé and Blank [43] investigated the available parallelism in a model of the 8080 microprocessor, consisting of 3439 gates, or LPs. Their study showed that, at any given time segment during the simulation, only 0.1-0.5% of the LPs were active and that only 10-20% of the LPs were active during each microprocessor clock cycle.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Soulé and Blank [43] investigated the available parallelism in a model of the 8080 microprocessor, consisting of 3439 gates, or LPs. Their study showed that, at any given time segment during the simulation, only 0.1-0.5% of the LPs were active and that only 10-20% of the LPs were active during each microprocessor clock cycle.…”
Section: Background and Related Workmentioning
confidence: 99%